Diagnostic Efficacy of Cardiac Isoenzyme CK-MB in Pericardial Fluid for Post-mortem Diagnosis of Myocardial Infarction - Ghormade, Pankaj Suresh; Kumar, Narendra Baluram; Tingne, Chaitanya Vidyadhar; Keoliya, Ajay Narmadaprasad (Journal of Indian Academy of Forensic Medicine, 2015)
Sudden cardiac death due to acute myocardial infarction is the most prevalent cause of death in  adults and constitutes a significant portion of the autopsies that are conducted by Forensic pathologists.  Serum cardiac isoenzymes Creatine phosphokinase-MB (CK-MB) has high sensitivity and specificity for  cardiac damage and routinely used for clinical diagnosis of myocardial infarction (MI). However, in  Forensic Medicine, diagnostic utility of this cardiac marker for post-mortem diagnosis of MI has not been  fully established. Present study is carried out with aim to evaluate the diagnostic efficacy of CK-MB in  pericardial fluid for autopsy diagnosis of MI. This study included 119 medico-legal autopsy cases selected  during a period of two years. Four study groups were formed depending upon final cause of death  Biochemical analysis of pericardial fluid was carried out. Highest levels of CK-MB were noted in deaths  due to IHD. By this cardiac marker, early infarcts can be predicted in sudden cardiac deaths associated  with severe coronary artery disease & inconclusive histopathological findings.  We obtained high diagnostic sensitivity and negative predictive value of CPK-MB for autopsy  diagnosis of MI in pericardial fluid comparable to the clinical analyses on serum.
Keywords: Autopsy; IHD; Myocardial infarction; Pericardial fluid; CPK-MB